Effect of Biochar Amendments on the Co-Composting of Food Waste and Livestock Manure - Woojin Chung; Jaehong Shim; Soon Woong Chang; Balasubramani Ravindran (Agronomy, 2022)
The global increase in population will result in increased global food production which can, in turn, lead to excessive food waste. Although composting is widely adopted for the conversion of organic waste into value-added products, there are several limitations, such as its lower efficiency in composting food waste without co-composting, the loss of nutrients, and the emission of greenhouse gases. Due to its renowned characteristics, biochar amendments are used during composting to overcome these issues; each waste should be at an appropriate level to yield good quality compost with high nutrient levels. In this study, we co-composted food waste with chicken and swine manure with varying proportions in the presence and absence of biochar to identify the ideal proportion of each raw material and the biochar. Physicochemical parameters such as pH, EC, temperature, bulk density, porosity, C:N ratio, and gaseous emissions were analyzed. The results showed that the desired quality of compost was obtained in the treatment with 5% biochar with 40%, 20%, and 20% of food waste, chicken manure, and swine manure, respectively, and 15% sawdust.